2002
DOI: 10.1055/s-2002-20125
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of Critical Speed, Critical Stroke Rate, and Anaerobic Capacity in Relation to Front Crawl Swimming Performances

Abstract: The purpose of this investigation was to determine whether the concepts of critical swimming speed, critical stroke rate and anaerobic swimming capacity could be used by coaches as a reliable index in order to monitor endurance performances in competitive swimmers. The results of this study conducted with well-trained swimmers showed that the 30-min test velocity (V30) is not different from the critical swimming speed determined from 200- and 400-m tests but is overestimated by 3.2 %. Furthermore, a regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
102
2
19

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(147 citation statements)
references
References 34 publications
(49 reference statements)
13
102
2
19
Order By: Relevance
“…This result confirms the findings in the literature, reinforcing the possibility to use the T-30 test as a determinant index of aerobic capacity in swimming (2,6,(8)(9)(10)(11) . Besides that, the mean concentration of peak lactate found at the end of the T-30 test was of 3.76 ± 1.65 mM, a value very close to the lactate concentration used in the test for VLan determination.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This result confirms the findings in the literature, reinforcing the possibility to use the T-30 test as a determinant index of aerobic capacity in swimming (2,6,(8)(9)(10)(11) . Besides that, the mean concentration of peak lactate found at the end of the T-30 test was of 3.76 ± 1.65 mM, a value very close to the lactate concentration used in the test for VLan determination.…”
Section: Discussionsupporting
confidence: 88%
“…Besides that, the mean concentration of peak lactate found at the end of the T-30 test was of 3.76 ± 1.65 mM, a value very close to the lactate concentration used in the test for VLan determination. Dekerle et al (8) observed peak lactate concentration of 3.65 ± 1.58 in the T-30 test, a value also close to 3.5 mM. Olbrecht et al (6) while using the steady concentration of 4 mM did not find significant difference either, besides finding a high correlation between the VLan and mean velocity in 30 minutes, with peak lactate concentration of 4.01 ± 0.75 mM.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Wakayoshi [42] and Dekerle [7] suggested that the field estimation of CV in swimmers requires only two performances (200m and 400m). In running Kranenburg and Smith [24] estimated lab CV using constant load tests on a treadmill that induced exhaustion within 3, 7 and 12 mins, and employed three set distances, each run on an indoor track, to estimate field CV.…”
mentioning
confidence: 99%